THE RISE OF REMOTE WORK AND ITS IMPACT ON BUSINESS PRODUCTIVITY - Dusmatov Begmuhammad Olimjonovich; Abdullaev Mirsaid Zohidjon oʻg‘li (Western European Studies, 2024)
The rise of remote work has become a significant trend in today's business landscape, driven by advancements in technology, changing workplace dynamics, and the global response to events such as the COVID-19 pandemic. This article explores the implications of remote work on business productivity, examining the benefits, challenges, and strategies for maximizing productivity in a remote work environment. Through an analysis of current trends and case studies, it offers insights into the impact of remote work on employee engagement, collaboration, and performance management. Additionally, it discusses the role of technology, organizational culture, and leadership in facilitating effective remote work practices and driving business productivity in the digital age
Keywords: Remote work; telecommuting; business productivity; work-from-home